A stylistic study of deviation in Certain Selected Poems by Alfred Lord Tennyson. - Al-Zubaidy, Fatima Hussein (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This work aims to elucidate deviations in poetic form. This study tries to deal with deviation in poetry style. Figurative language is known as a privilege status from the olden time and till now it is still commonly used by some speakers and writers. From different perspective , it is regarded as a magnificent and peculiar from all other sorts of language; which is deviant. The types of stylistic deviation found in the poetry find in this research have all analysed and tackled in different perspective . With this kind of deviation phenomenon whose data are based on selected samples from classical work in English poetry. This paper is limited to deal with deviation in English poetry, in particular, by the poet’s Alfred Lord Tennyson by analysis some selected poems of him. The present study tries to answer the following questions: 1. What is meant by deviation in English Language? 2. What are the types of deviation that are used in the selected data? 3. What is the most used types of deviation that are found in the data? The following answers are set: 1. Identifying the meaning of deviation in English Language. 2.Exploring and revealing types of deviation the selected data. 3.Clarifying the most used types of deviation that are found in the data.